MEMORIES ANALYSIS OF S.A. ESENIN CHILDHOOD AND ADOLESCENCE (TO THE 120TH ANNIVERSARY OF THE POET) - Заїка, Євген Валентинович (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
Based on the content analysis of poetry S.A. Esenina there were described his memories of childhood and youth, as well as his family, loved ones and others. There was conducted a detailed analysis of the content of his biographical memory giving its modalities (visual, auditory, kinesthetic), emotional coloring, and other parameters. We also isolated the main objects and situations, most often remembered by the poet, and especially memories of their people. There was shown the specificity of the poet’s memories of his childhood and adolescence; about his parents and the woman he loved. The material contributes to a better understanding and creative heritage and personality of the poet.